The 6-(10-Mercaptodecoxyl)quinoline self-assembled monolayer on gold : spectroscopy and wettability investigation - Zhang, Hua (2013)
A self-assembled monolayer (SAM) with an exposed basic group has been generated by the adsorption of a novel quinoline derivative 6-(10-mercaptodecoxyl)quinoline (MDQ) on a gold surface. The structure and surface properties of the SAMs of MDQ were characterized by ellipsometry, reflection absorption FTIR (RA-IR), and contact angle titration. It was found that the quinoline moiety of MDQ forms an ordered layer on the top of the film and the alkyl chain exhibits a packing density similar to that of a monolayer of decanethiol. The molecular orientation of MDQ in SAMs was evaluated by RA-IR spectroscopy which indicates that the alkyl chain exhibits a tilting angle of 24 ± 4° with respect to the surface normal and a twisting angle of 50 ± 5° around its axis. Contact angle titration in the pH range between 2 and 12 illustrates that the surface of SAM of MDQ is less hydrophilic for acidic solution than for basic solution, which is in contrast with the previous reports on SAMs that basic groups are located at the ends of the molecules.